The complete mitochondrial genome of an agamid lizard from the Afro–Asian subfamily agaminae and the phylogenetic position of Bufoniceps and Xenagama - Macey, J. Robert; Schulte II, James A.; Fong, Jonathan J.; Das, Indraneil; Papenfuss, Theodore J. (Elsevier Ltd., 2006)
Squamate reptiles are traditionally divided into six groups: Iguania, Anguimorpha, Scincomorpha, Gekkota (these four are lizards), Serpentes (snakes), and Amphisbaenia (the so-called worm lizards). The Iguania is recognized as having two major lineages the Iguanidae and Acrodonta (Agamidae and Chamaeleonidae). Currently, there are complete mitochondrial genomes from three Anguimorpha (Kumazawa, 2004; Kumazawa and Endo, 2004), two from the Scincomorpha (Kumazawa, 2004; Kumazawa and Nishida, 1999), one from Gekkota (Macey et al., 2005) two from Serpentes (Kumazawa, 2004; Kumazawa et al., 1998) and 12 from Amphisbaenia (Macey et al., 2004). In addition, two representatives of the Iguanian family Iguanidae (Janke et al., 2001; Kumazawa, 2004) have been sequenced. Its’ sister taxon, the Acrodonta, consists of seven monophyletic groups-the family Chamaeleonidae and six distantly related subfamilies of the family Agamidae (Macey et al., 2000b). Currently, the only acrodont lineage sequenced for the complete mitochondrial genome is Pogona vitticeps from the Australasian agamid subfamily Amphibolurinae (Amer and Kumazawa, 2005a).